Purified Cell Wall of Saccharomyces cerevisiae Increases Protection Against Intestinal Pathogens in Broiler Chickens - Baurhoo, B.; Goldflus, F.; Zhao, X. (International Journal of Poultry Science, 2009)
A study was conducted to determine effects of a mannanoligosaccharide prebiotic, derived from cell wall of the yeast Saccharomyces cerevisiae, on morphological development of the intestines and microbial populations of the ceca and litter. Dietary treatments included: antibiotic-free diet (CTL), diet 1 + virginiamycin (VIRG; 16.5 mg/kg feed) and diet 1 + ActiveMOS (MOS; 1.5 kg/T starter diet and 1 kg/T grower diet). Each treatment was assigned to 3 pen replicates (55 birds/pen). At day 14, 24 and 34, cecal contents were used for Lactobacilli, Bifidobacteria, E. coli and Campylobacter quantification whereas litter was analyzed for Campylobacter and E. coli. At same time points, jejunum samples were used in histological analysis. MOS significantly increased goblet cell number in the jejunum (p